18TH CENTURY ENGLISH ORIENTALISM PERSPECTIVE - Hasan BAKTIR (Fırat University, 2019)
In English literature there is an increasing interest in the Ottoman-orient during the 18th century. New literary genres that mainly deal with the Ottoman-Orient begin to appear in this period. Such new genres known as pseudo-oriental letters and oriental tales create a new perspective and challenge the traditional orientalist one. Pseudo-oriental letters become popular after the publication of Jean Paulo Marana’s Turkish Spy in 1684 and the genre is imitated by European writers. Montesquieu, in France, writes Persian Letters (1721); Oliver Goldsmith in England re-appropriates the genre in The Citizen of the World (1728). The mask used in the genre conceals the actual identity of the author. Thus, the author is free to criticize political and social corruptions. English writers interest in the Ottoman-orient continues to increase, after Pseudo-oriental Letters, with the translation of Thousand One Night Tales. Contemporary English authors produce works which either deal with the Orient or stories that take place in it. For instance, Samuel Johnson is one of them. These genres reflect the Orient from an intimate perspective. Therefore, 18th century English writers develop less prejudice and more intellectual tendency toward the Ottoman-orient. The present perspective is different from the traditional orientalist approach presented in Said’s Orientalism (1978). This article aims to explore how 18th century genres such as Pseudo-oriental letters, oriental tales and travel literature represent the Ottoman Orient and how such representation is different from the traditional European Orientalist Perspective.